Pelatihan Peningkatan Keterampilan Presentasi Bagi Siswa SMAN 1 Padang - ULFA, ULIA; Dewi, Mutia Rahmi; Jihan, Yulia; Rotama, Hendra; Sukma, Elfia (Jurnal Abdimas: Pengabdian dan Pengembangan Masyarakat, 2025)
This article contains community service program activities for lecturers in the Information Technology department, in order to fulfill the Tridharma of Padang State Polytechnic Higher Education for the 2024 fiscal year. The activities carried out are providing Presentation Skills Improvement Training for SMAN 1 Padang students with the aim of equipping students with good communication skills. effective, especially in the context of delivering material orally in public using the Canva application. This training is motivated by the importance of presentation skills in supporting academic and career success in the future. The methods used include lectures, interactive discussions, and direct practice involving presentation simulations. Participants were also given tips and techniques for mastering material, using body language, voice intonation, and managing nervousness when speaking in public. The results of this training showed a significant increase in students' confidence and their ability to use Canva and deliver structured and engaging presentations. Thus, it is hoped that this training can improve the quality of students' communication skills which are useful both in academic and social environments.